Quality of service provisioning in 802.11e networks challenges, approaches, and future directions. - Ramos, N. (IEEE Network : the magazine of global information exchange)
In order to support diverse application requirements, a new standard called IEEE 802.11e is being proposed to improve quality of service in wireless LAN networks. There are, however, a few remaining challenges that need to be addressed in order to enable comprehensive QoS support using 802.11e. In this article we provide an overview of a few of these challenges, describe their possible impact on QoS, and provide a survey of techniques that potentially could be used to address the identified challenges. Specifically, we focus on three challenges: handling time-varying network conditions, adapting to varying application profiles, and managing link layer resources. Additionally, we present several potential future directions toward improved QoS in wireless networks.